Comparison between Short Form-36 Health Status Questionnaires versus Quebec Back Pain Disability Scale on Acute Low Back Pain Patients - Dr.R.Raja; Dr.Trupti Milind Vedak; Dr.Somashekar (International Journal of Pharma and Bio Sciences, 2022)
The prevalence of low back pain in Indian population has been found by many researchers which ranges from 62% to 92% .The Quebec Disability Scale is a disease specific measure of disability associated with low back pain that has demonstrated good to excellent reliability and validity. Health related quality of life is measured using Short Form-36, used to examine health status in the following 8 domains: bodily pain, physical function, role limitations due to social problems, physical problems, general health, vitality, social function, mental health, role limitation due to physical problems. The aim of this study is to find the effect of Short Form-36 Health Status Questionnaire versus Quebec Disability Questionnaire to measure the pain, Range of Motion (ROM) and disability in subjects with acute low back pain treated with Interferential therapy and Mckenzie Back Extension Exercises. This is a longitudinal cohort study. A total of 120 patients were divided into two groups of 60 each. Each patient was given treatment for two weeks of Interferential therapy and McKenzie exercises. Group A patients were instructed to fill the Short Form-36 Health Status Questionnaire and Group B patients were instructed to fill the Quebec Disability Questionnaire and outcome measures were collected on day 1, at the end of week 1 and at the end of week 2. Data from study were analyzed using the statistical package SPSS 19.0 (SPSS Inc., Chicago, IL) and level of significance was set at p<0.05. Group B shows a mean of the total score of Quebec Disability Scale Questionnaire which was 57.11(SD 15.89) on Day 1; mean of 37.56 (SD 11.78) at the end of the first week and a mean of 21.31 (SD 11.13) at the end of second week. The p-value was found to be 0.0001. The percentage disability evaluated by the Quebec Disability Questionnaire shows a mean of 46.18on Day 1; mean of 22.55 at the end of first week and a mean of 2.31 at the end of second week. On day 1 Short Form-36 Questionnaire, total score of group A was 96.76 ; mean of 98.36 at the end of first week and mean of 100.95 (SD 6, with statistically significant difference p-value (0.008). Thus the present study showed that Quebec Back Pain Disability Questionnaire had superior sensitivity in reducing pain and increasing range of motion and thus by decreasing the disability.